The aesthetic impact of graffiti art on the modern Greek urban landscape - Tsoumas, Johannis (Ángulo Recto. Revista de estudios sobre la ciudad como espacio plural, 2011)
Graffiti art is an expression of modern culture and, at the same time, it constitutes a counterculture in itself. Being ephemeral by nature, graffiti is an art form that celebrates change and feeds on new ideas. The street is a unique and powerful platform, a frontline where it can be expressed, transmitting personal or collective visions directly to the public at the same way as official messages. In the last two decades Greece has experienced both the effects and the side effects of globalization, from which the graffiti phenomenon would not have been excluded. The new sociopolitical and economic status quo of Greece constituted the ideal basis on which graffiti art could thrive on as it enhanced and encouraged both its ideological and aesthetic values which were meant to fight against social inequality and public litter caused by commercial advertising. However, the variety of street art and its expansion on almost every public surface of the big Greek cities, became soon a new problematic for both the citizens and the state which invented ways to face it. This research aims to focus mainly on the aesthetic impact of graffiti on the modern Greek urban landscape not only as a phenomenal way of expression, but also as a new means of controlled decoration imposed by the local authorities and the government.